2001
DOI: 10.1051/0004-6361:20011073
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic monitoring of the jet in the symbiotic star MWC 560

Abstract: Abstract. We present the results of an intensive monitoring program of the jet absorptions in the symbiotic system MWC 560, obtained with the FEROS echelle spectrograph at the ESO 1.5 m Telescope. MWC 560 is a unique jet source because the line of sight lies practically parallel to the jet axis so that the outflowing gas is seen as absorption in the continuum of the accreting object, in the emission line spectrum of the accretion disk and temporary also in the spectrum of the red giant companion. Highly variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
72
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(79 citation statements)
references
References 51 publications
(54 reference statements)
7
72
0
Order By: Relevance
“…The jet (orbit) inclination angle to the line of sight is i < 16 • , and the white dwarf accretes at a rateṀ acc ≈ 5 × 10 −7 M ⊙ (Schmid et al 2001). …”
Section: Tidal Interaction In Mwc 560mentioning
confidence: 99%
See 2 more Smart Citations
“…The jet (orbit) inclination angle to the line of sight is i < 16 • , and the white dwarf accretes at a rateṀ acc ≈ 5 × 10 −7 M ⊙ (Schmid et al 2001). …”
Section: Tidal Interaction In Mwc 560mentioning
confidence: 99%
“…In the case of MWC 560, we can estimate from the rate of accretion on the white dwarf,Ṁ acc ≈ 5 × 10 −7 M ⊙ (Schmid et al 2001), that it will take 10 6 yr to accrete ∼ 0.5 M ⊙ from the envelope of the red giant companion. Because the giant also losses mass via stellar wind, we find that the lifetime of the symbiotic phase of MWC 560 should be τ ss < ∼ 10 6 yr.…”
Section: Lifetime Of the Symbiotic Phasementioning
confidence: 99%
See 1 more Smart Citation
“…Thus the absorption must be caused by material close to the central white dwarf. Our own calculations showed that the column density of the jet is only of the order of 10 22 cm −2 Schmid et al 2001) or below, thus the high column density derived from our data cannot be attributed to the jet.…”
Section: The Hard Component Of the Spectrummentioning
confidence: 49%
“…While these two objects are seen at high inclinations, in MWC 560 (or V694 Mon) the jet axis is practically parallel to the line of sight (Tomov et al 1990;Schmid et al 2001). This special orientation allows one to observe the outflowing gas as line absorption in the source spectrum.…”
Section: Introductionmentioning
confidence: 98%